1971
DOI: 10.1128/iai.4.1.20-22.1971
|View full text |Cite
|
Sign up to set email alerts
|

Complement-Fixing Antigens in Burkitt Lymphoma Cell Lines

Abstract: The complement-fixing (CF) activity of antigens from cultured Burkitt lymphoma cells was determined by using normal American sera as the source of antibody. Approximately 75 % of the sera fixed complement with the positive cell lines. These lines contained the herpes-like virus detectable by electron microscopy. The content of CF antigen depended on the cell line used but appeared to be independent of the number of cells which produced Henle's immunofluorescence (IF) antigen. Only sera that reacted in the IF t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1972
1972
1996
1996

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The CF activity of extracts from these cultures did not follow the pattern established for the Burkitt cell lines; i.e., the presence of the herpes particle as detected by electron microscopy did not correlate with the presence of CF antigen in the American lines when tested against African sera. However, since Henle's antigen was detected sporadically in the OP cell line, the relationship between the presence of this antigen and CF reactivity was still maintained (7).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The CF activity of extracts from these cultures did not follow the pattern established for the Burkitt cell lines; i.e., the presence of the herpes particle as detected by electron microscopy did not correlate with the presence of CF antigen in the American lines when tested against African sera. However, since Henle's antigen was detected sporadically in the OP cell line, the relationship between the presence of this antigen and CF reactivity was still maintained (7).…”
Section: Resultsmentioning
confidence: 99%
“…Complement-fixing (CF) antigen(s) in extracts from lymphoid cell lines have been described by several investigators (1,3,7,8,13,14,(16)(17)(18). These studies have indicated that humoral antibodies to the antigen(s) are related to infection of the individual by the herpes-like virus present in lymphoid cell cultures.…”
mentioning
confidence: 99%
See 3 more Smart Citations